Editorial: tailoring mycophenolate mofetil rescue therapy for success in autoimmune hepatitis—authors' reply. Issue 11 (10th May 2019) - Nicoll, Amanda J.; Roberts, Stuart K.; Strasser, Simone I.; ,
Abstract : Linked Content This article is linked to Nicoll et al and Czaja papers. To view these articles, visithttps://doi.org/10.1111/apt.15248 andhttps://doi.org/10.1111/apt.15272 .